Optimizing Epilepsy Management In The Elderly: A Cohort Study Comparing Brivacetam And Levetiracetam - Ramya, C Vincy; Karthickeyan, K; Shanmugasundaram, P. (Journal of Neonatal Surgery, 2025)
Background: Managing epilepsy in older people is more difficult because of changes in how drugs work with age, cognitive decline, and a greater risk of side effects. Levetiracetam and Brivaracetam are newer-generation antiepileptic drugs (AEDs) that are often prescribed. However, there is still not enough real-world data comparing their safety, tolerability, and effects on quality of life in older people. Objective: To see how levetiracetam and brivaracetam monotherapy affect the quality of life, seizure control, cognition, mood, frailty, and safety of older people with epilepsy over a 24-week treatment period. Methods: This was a 24-week, open-label, observational cohort study done at a tertiary care hospital in Chennai, India. We enrolled 80 people with epilepsy who were at least 65 years old and divided them into two groups of 40 based on whether they were currently taking levetiracetam or brivaracetam. The Older People's Quality of Life Questionnaire (OPQOL-35), the Mini-Mental State Examination (MMSE), the Geriatric Depression Scale (GDS-15), the Clinical Frailty Scale (CFS), and seizure diaries were all used for baseline and follow-up assessments. We checked compliance every month and kept track of any bad things that happened during the study. Results: At 24 weeks, both groups had significant improvements in their OPQOL-35 scores, but brivaracetam had a bigger mean improvement than levetiracetam (Δ = 5.4 points; p = 0.038). Both groups saw improvements in cognitive function and mood, but brivaracetam had a statistically significant edge in MMSE and GDS-15 change scores. Adverse events happened more often in the levetiracetam group (35%) than in the brivaracetam group (20%). Most of these events were mild neuropsychiatric or systemic symptoms. Conclusion: Brivaracetam was better tolerated and led to bigger improvements in quality of life and cognitive measures than levetiracetam. This supports its use in older people with epilepsy.